Insulating heat conductive sheet
By making boron nitride highly oriented and controlling the crosslinking structure of silicone resin in the heat-conducting sheet, the problems of high hardness and low reliability of the existing heat-conducting sheet are solved, and high thermal conductivity and softness in the thickness direction are achieved , ensuring electrical insulation and long-term reliability.
Patent Information
- Application Number
- CN202380042212.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-25
- Filing Date
- 2023-05-16
- Publication Date
- 2025-01-03
AI Technical Summary
Due to the high filling rate, the existing heat conducting sheets have increased hardness, which reduces the adhesion with the heating component, which cannot fully exert heat dissipation, and there are expansion/contraction problems when the temperature changes, which affects long-term reliability.
By oriented boron nitride and controlling the crosslinking structure of the silicone resin, an insulating heat conductivity sheet with excellent thermal conductivity and softness in the thickness direction was prepared, and a specific thermosetting silicone resin and boron nitride composition were used to prepare a thermally curable silicone resin and boron nitride composition. , combined with the average particle size and aspect ratio detected by laser diffraction/scattering method, ensure the thermal conduction and electrical insulation of the sheet.
High thermal conductivity and low hardness in the thickness direction are achieved, the softness and electrical insulation of the sheet are ensured, and the adhesion and long-term reliability are improved with the heating components.
Smart Images

Figure CN119256396A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a thermally conductive sheet having electrical insulating properties. Background Art
[0002] In recent years, with the further improvement of the performance of electronic devices, the high density and high packaging of semiconductor elements have been continuously promoted. Along with this, the heat generated by the electronic components constituting the electronic devices is also increasing, so it is important to dissipate heat effectively. In contrast, in order to dissipate the heat generated by the heating element, a heat sink such as a radiator is generally used. It is known that the heat dissipation sheet is arranged between the heating element and the heat sink for the purpose of improving the thermal conductivity.
[0003] In particular, the electrification of automobiles is significant, and the number of electronic components installed has increased. Therefore, the demand for heat dissipation components is also increasing. Among heat dissipation components, although there are sheet types and grease types, most people prefer to use sheet types from the perspective of ease of installation. In addition, in heat dissipation components such as those used in the context of autonomous driving, it is required to further improve thermal conductivity. Usually, in order to achieve high thermal conductivity, it is necessary to increase the filling rate of fillers dispersed in the polymer, so the specific gravity tends to increase. Therefore, there are still problems in improving the fuel consumption of gasoline-powered vehicles, the electricity cost of EV vehicles, and promoting lightweighting.
[0004] For example, Patent Document 1 proposes a method for producing a thermally conductive resin sheet. The method for producing a thermally conductive resin sheet at least comprises: a curing step of obtaining a cured product by curing the extruded product by extruding a thermally conductive composition containing a polymer, an anisotropic filler, and a filler using an extruder, and a cutting step of cutting the cured product into a predetermined thickness in a direction perpendicular to the extrusion direction using an ultrasonic cutter.
[0005] In addition, for example, Patent Document 2 proposes a method for producing a thermally conductive sheet. The method for producing a thermally conductive sheet includes applying a magnetic field to a thermally conductive composition containing a polymer, an anisotropic filler, and a filler to orient the anisotropic thermally conductive filler to form a bulk molded body, and slicing the body into a desired sheet thickness.
[0006] In addition, for example, Patent Document 3 proposes a method for producing a thermally conductive sheet. The method for producing a thermally conductive sheet comprises calendering, extrusion molding, extrusion molding, or coating a thermally conductive composition containing a polymer, an anisotropic filler, and a filler to a thickness of 20 times or less of the average length of the anisotropic filler to produce an oriented primary sheet, and slicing a molded body on which the primary sheets are laminated.
[0007] Furthermore, a method for producing an insulating heat conductive sheet is also proposed in Patent Document 4. The method for producing an insulating heat conductive sheet comprises producing a primary sheet in which flat boron nitride is highly filled in an aramid resin and oriented, and then slicing the molded body coated and laminated with an insulating adhesive layer.
[0008] However, the heat conductive sheets obtained by the conventional methods tend to have a higher hardness due to the high filling and orientation of anisotropic fillers such as boron nitride. Therefore, the heat conductive sheets obtained by the conventional methods have a problem of reduced adhesion with the heat generating components and inability to fully exert heat dissipation. In addition, the heat conductive sheet generally expands and contracts due to the temperature rise and fall of the heat generating component. Therefore, when the lamination interface is composed of different materials or hardness, there are great concerns about long-term reliability. Prior art literature Patent Literature
[0009] [Patent Document 1]: Japanese Patent Application Publication No. 2012-023335 [Patent Document 2]: Japanese Patent Application Publication No. 2019-186555 [Patent Document 3]: Japanese Patent Application Publication No. 2017-126614 [Patent Document 4]: International Publication No. 2021 / 090929 Summary of the invention Problem that the invention aims to solve
[0010] Therefore, an object of the present invention is to provide an insulating thermally conductive sheet which is excellent in thermal conductivity in the thickness direction and is flexible. Solutions to the problem
[0011] As a result of intensive studies, the present inventors have found that a flexible insulating thermally conductive sheet having excellent thermal conductivity in the thickness direction can be obtained by highly orienting boron nitride and controlling the crosslinking structure of a silicone resin, thereby completing the present invention. That is, the present invention provides the following insulating thermally conductive sheet. [1] An insulating thermally conductive sheet is a cured product of a thermally conductive silicone resin composition, comprising the following components (A) and (B), (A) 100 parts by mass of a thermosetting silicone resin containing the following (A1) to (A3), wherein: (A1) an organopolysiloxane having two or more alkenyl groups bonded to a silicon atom in one molecule, (A2) an organohydrogenpolysiloxane composed of the following (A2-a) and (A2-b), wherein the molar ratio of the total amount of hydrosilyl groups in the component (A2) to the alkenyl groups bonded to silicon atoms in the component (A1) is 0.7 to 1.2, (A2-a) an organohydrogenpolysiloxane represented by the following formula (a), [Chemical formula 1] (In the formula, m is 2 or 3, n is a number from 10 to 50, and the bonding sequence of each siloxane unit bracketed by m and n may be block or random) (A2-b) an organohydrogenpolysiloxane represented by the following formula (b), [Chemical formula 2] (In the formula, p is a number between 10 and 30), (the molar ratio of the above-mentioned component (A2-a) to the component (A2-b) is (A2-a) component: (A2-b) component = 1:0.2 to 1:2), (A3) Hydrosilylation catalyst: an amount of 100 to 3000 ppm in terms of platinum group metal atoms relative to 100 parts by mass of the component (A1); (B) boron nitride having an average particle size of 40 to 100 μm and an aspect ratio of 20 to 100 as detected by a laser diffraction / scattering method: 150 to 500 parts by mass, The insulating heat conductive sheet has a degree of orientation in a thickness direction detected by an X-ray diffraction method that satisfies the sum of count values of [2θ=41 to 43°] / the sum of count values of [2θ=25 to 27°]=1 or more. [2] The insulating heat-conductive sheet as described in [1] has an Asker C hardness of 20 to 60. [3] The insulating heat-conductive sheet according to [1] or [2] has a thermal conductivity in the thickness direction of 16 to 30 W / mK. [4] The insulating heat conductive sheet according to any one of [1] to [3] has a dielectric breakdown voltage of 5 kV / mm or more. [5] The insulating heat-conductive sheet according to any one of [1] to [4], wherein the specific gravity is 1.2 to 2.0. Effects of the Invention
[0013] The insulating thermally conductive sheet of the present invention has excellent thermal conductivity in the thickness direction and excellent electrical insulation, and has low hardness and excellent flexibility. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] [ Figure 1 ] is a three-dimensional diagram showing an example of a mold used in the filling process. [ Figure 2 ] is to indicate Figure 1 A cross-sectional view of the cross-sectional structure of the mold. [ Figure 3 ] is a disassembled stereoscopic view showing an example of a mold used in a molding process. DETAILED DESCRIPTION
[0015] Hereinafter, the present invention will be described in detail, but the present invention is not limited thereto. [Insulating heat conductive sheet] The insulating thermally conductive sheet of the present invention is a cured product of a thermally conductive silicone resin composition containing a thermosetting silicone resin and boron nitride, preferably an insulating thermally conductive sheet obtained by molding a thermally conductive silicone resin composition containing boron nitride in a thermosetting silicone resin by a method described below. The details are described below.
[0016] [Thermal conductive silicone resin composition] The heat conductive silicone resin composition is characterized by containing (A) a thermosetting silicone resin and (B) boron nitride. The (A) thermosetting silicone resin is a thermosetting silicone resin (addition curing organopolysiloxane composition) containing the following (A1) to (A3). (A1) an organopolysiloxane having two or more alkenyl groups bonded to a silicon atom in one molecule; (A2) an organohydrogenpolysiloxane; (A3) a hydrosilylation catalyst
[0017] [(A1) an organopolysiloxane having two or more alkenyl groups bonded to a silicon atom in one molecule] The component (A1) is an organopolysiloxane having two or more alkenyl groups bonded to silicon atoms in one molecule, and is the main component of the thermally conductive silicone resin composition. Generally, the main chain portion is generally basically composed of diorganosiloxane units repeating. It should be noted that a part of the molecular structure may contain a branched structure or a cyclic body, but from the perspective of physical properties such as mechanical strength of the cured product, a linear diorganopolysiloxane is preferred. Examples of the alkenyl group include vinyl, allyl, propenyl, isopropenyl, butenyl, hexenyl, cyclohexenyl, and the like, which are alkenyl groups generally having about 2 to 8 carbon atoms, and among them, vinyl, allyl, and other lower alkenyl groups having 2 to 4 carbon atoms are preferred, and vinyl is particularly preferred. It should be noted that there should be two or more alkenyl groups in one molecule, and in order to obtain a cured product with good flexibility, the component (A1) is more preferably an organopolysiloxane having alkenyl groups bonded only to silicon atoms at both ends of the molecular chain. As the group bonded to the silicon atom other than the alkenyl group, a monovalent hydrocarbon group is preferably a group having 1 to 10 carbon atoms, and particularly preferably a group having 1 to 6 carbon atoms. Examples of the monovalent hydrocarbon group include alkyl groups such as methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl, neopentyl, hexyl, heptyl, octyl, nonyl, and decyl; cycloalkyl groups such as cyclopentyl, cyclohexyl, and cycloheptyl; aryl groups such as phenyl, tolyl, xylyl, and naphthyl; aralkyl groups such as benzyl, phenylethyl, phenylpropyl, and methylbenzyl. Alkyl groups having 1 to 3 carbon atoms such as methyl, ethyl, and propyl, and phenyl are preferred. In addition, the group bonded to the silicon atom other than the alkenyl group is not limited to all being the same, and may be a group in which different groups are bonded to the silicon atom. The kinematic viscosity of the organopolysiloxane of the component (A1) at 25° C. is preferably in the range of 10 to 100,000 mm / s. 2 / s, particularly preferably in the range of 100-100000mm 2 / s range. If the kinematic viscosity is within 10mm 2 / s or more, the storage stability of the obtained resin composition is good. In addition, if the kinematic viscosity is 100000mm 2 / s or less, the ductility of the obtained resin composition will not be deteriorated. In addition, in this specification, the kinematic viscosity is a value at 25° C. using a Cannon Fenske viscometer described in JIS Z8803:2011. The organopolysiloxane of the component (A1) may be used alone or in combination of two or more types having different structures or kinematic viscosities.
[0018] [(A2) Organohydrogenpolysiloxane] The component (A2) is an organohydrogenpolysiloxane, which is characterized by being a mixture of the following components (A2-a) and (A2-b).
[0019] (A2-a) An organohydrogenpolysiloxane represented by the following formula (a). [Chemical formula 3] (m is 2 or 3, n is a number from 10 to 50, and the bonding order of each siloxane unit bracketed by m and n may be block or random.)
[0020] (A2-b) an organohydrogenpolysiloxane represented by the following formula (b): [Chemical formula 4] (p is a number between 10 and 30.)
[0021] The organohydrogenpolysiloxane of the component (A2-a) is an organohydrogenpolysiloxane having two or three hydrogen atoms (hydrogen silyl groups) directly bonded to silicon atoms in one molecule, and is a component that functions as a crosslinking agent for the component (A1). That is, the hydrosilyl groups in the component (A2-a) are added to the alkenyl groups in the component (A1) by a hydrosilylation reaction promoted by a hydrosilylation catalyst of the component (A3) described later, thereby obtaining a three-dimensional network structure. On the other hand, even when the organohydrogenpolysiloxane having only hydrosilyl groups at both terminals as component (A2-b) is added to the alkenyl group in component (A1), it only extends the molecular chain and does not inhibit the free movement of molecules.
[0022] The molar ratio of component (A2-a) to component (A2-b) is component (A2-a):component (A2-b) = 1:0.2 to 1:2, more preferably 1:0.3 to 1:1.6, and even more preferably 1:0.4 to 1:0.8. When the ratio of component (A2-a):component (A2-b) is less than 1:0.2, the ratio of chain length extension decreases, and the flexibility of the cured product is impaired. On the contrary, when the ratio of component (A2-a):component (A2-b) is greater than 1:2, the ratio of the three-dimensional crosslinked structure decreases, and curing of the composition becomes difficult.
[0023] The amount of component (A2) added is such that the amount of hydrosilyl groups derived from component (A2) is 0.7 to 1.2 moles relative to 1 mole of alkenyl groups derived from component (A1) (i.e., the number of moles of hydrosilyl groups is 0.7 to 1.2 times the number of moles of alkenyl groups derived from component (A1)). If the amount of hydrosilyl groups derived from component (A2) is less than 0.7 moles relative to 1 mole of alkenyl groups derived from component (A1), no curing will occur. In addition, if the amount of hydrosilyl groups derived from component (A2) is greater than 1.2 moles relative to 1 mole of alkenyl groups derived from component (A1), the softness of the cured product will disappear, and the cured product may become brittle.
[0024] [(A3) Hydrosilylation Catalyst] The hydrosilylation catalyst of component (A3) is a catalyst for promoting the addition reaction of the alkenyl group from component (A1) and the hydrosilyl group from component (A2). As the catalyst used for the hydrosilylation reaction, known catalysts can be listed. Specific examples thereof include single substances of platinum group metals such as platinum (including platinum black), rhodium, and palladium; 2 PtCl 4 ·nH 2 O, H 2 PtCl 6 ·nH 2 O、NaHPtCl 6 ·nH 2 O、KHPtCl 6 ·nH 2 O、Na 2 PtCl 6 ·nH 2 O.K 2 PtCl 4 ·nH 2 O、PtCl 4 ·nH 2 O、PtCl 2 、Na 2 HPtCl 4 ·nH 2 O (however, in the formula, n is an integer of 0 to 6, preferably 0 or 6.) chloroplatinum, chloroplatinic acid and chloroplatinates; alcohol-modified chloroplatinic acid (see U.S. Patent No. 3,220,972); complexes of chloroplatinic acid and olefins (see U.S. Patent No. 3,159,601, U.S. Patent No. 3,159,662, and U.S. Patent No. 3,775,452); substances in which platinum group metals such as platinum black and palladium are supported on carriers such as alumina, silica, and carbon; rhodium-olefin complexes; tris(triphenylphosphine)rhodium chloride (Wilkinson catalyst); complexes of chloroplatinum, chloroplatinic acid or chloroplatinate and vinyl-containing siloxanes, especially complexes of chloroplatinum, chloroplatinic acid or chloroplatinate and vinyl-containing cyclic siloxanes, etc. The content of component (A3) is 100 to 3000 ppm, preferably 100 to 2000 ppm, calculated as the mass of the platinum group metal element relative to component (A1). If the content of component (A3) is 100 ppm or more, sufficient catalytic activity can be obtained; if the content of component (A3) is 3000 ppm or less, the effect of promoting the addition reaction is sufficient and the cost is also suppressed.
[0025] [(B) Boron nitride] The boron nitride of the component (B) is a particle that is oriented in the thickness direction of the insulating heat conductive sheet (hereinafter referred to as the "sheet") and promotes heat conduction. From the viewpoint of heat conduction and electrical insulation in the thickness direction of the sheet, the boron nitride of the component (B) is particularly preferably hexagonal boron nitride. Moreover, its shape has a specific average particle size and aspect ratio as described later, and is preferably flat, flaky, plate-like or flake-like.
[0026] The aspect ratio of boron nitride is 20 to 100, preferably 30 to 100, and more preferably 50 to 100. When the aspect ratio is 20 or more, since heat conduction can be improved, important orientation can be ensured, thereby providing high heat conduction in the thickness direction of the sheet. In addition, when the aspect ratio is 100 or less, the flexibility of the sheet can be maintained. In this specification, the aspect ratio is the value obtained by dividing the major diameter of the particle by the thickness of the particle, that is, major diameter / thickness. When the particle is spherical, the aspect ratio is 1, and the aspect ratio increases as the degree of flatness increases. In this specification, the aspect ratio is a value obtained by measuring the major diameter and thickness of a particle at a magnification of 1500 times using a scanning electron microscope and calculating the major diameter / thickness.
[0027] The average particle size of the boron nitride is 40 to 100 μm, more preferably 40 to 90 μm, and particularly preferably 50 to 80 μm. In order to impart flexibility to the sheet, it is necessary to effectively form a heat conduction path in the thickness direction. If the average particle size of the boron nitride is less than 40 μm, the thermal conductivity is insufficient. In addition, if the average particle size of the boron nitride is greater than 100 μm, the flexibility of the sheet is impaired. Boron nitride having a single average particle size may be used, or a mixture of multiple boron nitrides having different average particle sizes may be used. The average particle size is the median particle size measured by a laser diffraction / scattering method using a laser diffraction / scattering particle size distribution measuring apparatus (the particle size at which particles larger than a certain particle size and particles smaller than the particle size become equal when a powder is divided into two at a certain particle size, generally also referred to as D50).
[0028] The content of boron nitride is 150 to 500 parts by mass, preferably 200 to 400 parts by mass, relative to 100 parts by mass of component (A). When the content of boron nitride is less than 150 parts by mass relative to 100 parts by mass of component (A), sufficient thermal conductivity cannot be obtained in the thickness direction of the sheet; when the content of boron nitride is greater than 500 parts by mass relative to 100 parts by mass of component (A), the sheet becomes hard and lacks flexibility.
[0029] In addition, within the range that does not hinder the orientation of boron nitride, insulating inorganic particles such as aluminum oxide, magnesium oxide, aluminum hydroxide, aluminum nitride, silicon nitride, and silicon dioxide may also be used in combination. By using other insulating inorganic particles in combination, the viscosity of the composition can be adjusted, so it is sometimes preferred from the perspective of processability.
[0030] [Other ingredients] The thermally conductive silicone resin composition may further contain components such as a solvent, a thixotropy imparting agent, a dispersant, a curing agent, a curing accelerator, a retarder, a micro-adhesion imparting agent, a plasticizer, a flame retardant, an antioxidant, a stabilizer, and a colorant as required.
[0031] In addition, the thermally conductive silicone resin composition may also contain fillers other than the component (B). Specifically, silicon dioxide, titanium oxide, etc. may be mentioned. The amount of the filler is not particularly limited as long as it does not impair the effect of the present invention, but the amount of the filler is preferably 0 to 60 parts by mass, more preferably 0 to 40 parts by mass, relative to 100 parts by mass of the component (A).
[0032] [Method for producing thermally conductive silicone resin composition] The thermally conductive silicone resin composition can be produced by mixing (A) the thermosetting silicone resin and (B) boron nitride using a stirrer or the like, and further mixing the other components as necessary. The (A) thermosetting silicone resin may be mixed with the (B) boron nitride etc. after premixing the (A1) component, the (A2) component consisting of (A2-a) and (A2-b), and the (A3) component using a mixer etc., or may be mixed together with the (B) boron nitride etc. without premixing.
[0033] [Method for producing insulating heat-conductive sheet] The method for producing the insulating thermally conductive sheet of the present invention includes a step of molding the thermally conductive silicone resin composition and a step of curing the composition, and for example, the following method can be mentioned.
[0034] [Method for producing insulating heat-conductive sheet (1)] An example of a method for producing the insulating thermally conductive sheet of the present invention is a production method (1) comprising the following steps: A filling step of filling the heat conductive silicone resin composition into the mold; The vibration process uses ultrasonic waves to vibrate the mold to remove bubbles and orient the boron nitride; A heating step, in which the heat-conductive silicone resin composition is heated to obtain a semi-cured silicone composition in the form of an elongated strip; The molding process is to place the elongated semi-cured silicone composition in the length direction, and heat and pressurize it to obtain a thermally conductive silicone molding; In the slicing step, the thermally conductive silicone molded body is sliced to obtain an insulating thermally conductive sheet having a desired thickness. According to this production method, by highly orienting boron nitride, it is possible to obtain a flexible insulating thermally conductive sheet having excellent thermal conductivity in the thickness direction. Hereinafter, each step of the production method (1) will be described in detail.
[0035] Filling process (1) (Mold used for filling process) The width of the mold used in the filling process is less than 5.0 mm, the depth is greater than the width length + 1.0 mm, and the length is greater than 10.0 mm. There is no particular limitation on the shape of the bottom surface, and wedge-shaped, semicircular, wavy, and flat shapes are listed, and the mold has one or more grooves. Figure 1 is a perspective view showing an example of a mold used in a filling process. Figure 2 for Figure 1 A cross-sectional view of the mold at line AA is shown.
[0036] (Filling method) In the filling step, a predetermined amount of the thermally conductive silicone resin composition may be filled into the groove of the mold, or after a large amount of the thermally conductive silicone resin composition is filled, an excess amount may be scraped off with a scraper or the like. If a solvent is added to the thermally conductive silicone resin composition, the viscosity of the composition is reduced and the filling property is improved, which is preferred. In addition, when degassing and settling the boron nitride in the next step of vibration, the long axis direction of the boron nitride is easily oriented in the long axis direction of the elongated semi-cured silicone composition.
[0037] Vibration process (1) The vibration step is a step for vibrating the mold filled with the thermally conductive silicone resin composition by ultrasonic waves to degas and orient the boron nitride. In order to obtain a long and thin strip of semi-cured silicone composition in the next step of heating, the mold is vibrated by ultrasonic waves to degas and precipitate and orient the boron nitride, so that the long axis direction of the boron nitride can be oriented in the long axis direction of the long and thin strip of semi-cured silicone composition. The frequency of the vibration step is preferably 28 to 120 kHz, more preferably 40 to 120 kHz. In addition, the temperature of the silicone resin composition during the vibration step is preferably 40° C. or lower so as not to promote the curing reaction.
[0038] Heating process (1) The heating step is a step of filling the heat-conductive silicone resin composition and heating the heat-conductive silicone resin composition in the mold after the vibration step to obtain a thin and long strip of semi-cured silicone composition along the shape of the groove of the mold. If the heat-conductive silicone resin composition contains a solvent, it also includes a step of volatilizing the solvent component by heating. The heating temperature of the heating step is preferably 40 to 100°C, more preferably 60 to 80°C. In addition, the heating time is preferably 1 to 30 minutes, more preferably 1 to 10 minutes.
[0039] Molding process (1) (Molds used in the molding process) The mold used in the molding process is characterized in that it has a lower mold and an upper mold, the lower mold is a concave mold with internal dimensions of 10.0 mm or more in width, 10.0 mm or more in length, and 10.0 mm or more in depth, and the bottom surface shape is flat, and the width and length of the upper mold are respectively 0.01 to 0.2 mm shorter than the internal dimensions of the lower mold. There is no particular restriction on the height of the upper mold, but a height that can pressurize the upper mold is required. Figure 3 This is an exploded perspective view showing an example of a mold used in the molding process. Figure 3 The mold used for the molding process is represented as a mold having an internal dimension of a lower mold with a width of 33.0 mm (X axis), a length of 52.0 mm (Y axis), and a depth of 50.0 mm (Z axis) and an upper mold with a width of 32.9 mm (X axis), a length of 51.9 mm (Y axis), and a height of 40.0 mm (Z axis).
[0040] (Filling method) The elongated strip-shaped semi-cured silicone composition obtained in the heating step is filled in the lower mold in the following manner (i) or (ii). (i) The long and thin strips of semi-cured silicone composition are arranged in the X-axis direction of the mold in such a manner that the length direction thereof is parallel to the X-axis direction, and are stacked and filled in the Z-axis direction. (ii) The long and thin strips of semi-cured silicone composition are arranged in the Y-axis direction of the mold in such a manner that the length direction thereof is parallel to the Y-axis direction, and are stacked and filled in the Z-axis direction. By adopting such a filling method, a molded body in which boron nitride is oriented can be obtained more preferably and efficiently. There is no particular restriction on the number of the elongated strips of semi-cured silicone composition arranged in the X-axis direction or the Y-axis direction, and it can be appropriately determined based on the size of the lower mold, the size of the elongated strips of semi-cured silicone composition, etc. From the perspective of production capacity, for example, 2 to 5,000 are preferred, and 5 to 3,000 are more preferred. The number of the elongated strips of semi-cured silicone composition deposited in the Z-axis direction is preferably 2 or more (2 layers), and more preferably 5 to 3,000 (5 to 3,000 layers).
[0041] (Molding method) The molding step is a step of pressing the lower mold with the upper mold in the Z-axis direction and completely curing the elongated strip-shaped semi-cured silicone composition by heating to obtain a thermally conductive silicone molded body. As a pressurization method, it is preferable to gradually increase the pressure from atmospheric pressure to reach a desired pressure. The pressure for pressing the mold can be appropriately selected depending on the desired shape and hardness of the thermally conductive silicone molded body, and is preferably 0.1 to 20.0 MPa, and more preferably 0.5 to 5.0 MPa. The surface temperature of the lower mold when the mold is pressurized is preferably -10 to 40°C, more preferably 0 to 30°C. The surface temperature of the lower mold during curing of the elongated strip-shaped semi-cured silicone composition is preferably 50 to 200° C., more preferably 100 to 150° C. In addition, the curing time is preferably 1 minute to 24 hours, more preferably 5 minutes to 1 hour.
[0042] Slicing process (1) The slicing step is a step of obtaining an insulating thermally conductive sheet having a desired thickness by slicing the thermally conductive silicone molded body obtained in the molding step. Specifically, in the molding step, when filling by the method (i), the molded body is sliced to a desired thickness in parallel with the YZ plane; when filling by the method (ii), the molded body is sliced to a desired thickness in parallel with the XZ plane, thereby obtaining an insulating thermally conductive sheet having the longitudinal direction of boron nitride oriented in the thickness direction of the sheet.
[0043] [Method for producing insulating heat-conductive sheet (2)] In addition, as a method for producing the insulating thermally conductive sheet of the present invention which is different from the above-mentioned production method, there can be cited a production method (2) which includes the following steps: A coating step of coating the thermally conductive silicone resin composition on the separator in a uniform thickness using a Baker-type film coater or the like; A heating step of obtaining a sheet-like semi-cured silicone composition from the thermally conductive silicone resin composition by heating; a cutting step of peeling the thermally conductive silicone resin composition from the separator and cutting it according to the size of the mold used in the molding step; A molding step, arranging the sheet-like semi-cured silicone composition in the coating direction and heating and pressurizing it to obtain a thermally conductive silicone molded body; In the slicing step, the thermally conductive silicone molded body is sliced to obtain a thermally conductive sheet having a desired thickness. Hereinafter, each step of the production method (2) will be described in detail.
[0044] Coating process (2) The coating step is a step of coating the thermally conductive silicone resin composition in a uniform thickness on a separator film that can be peeled off the sheet-like semi-cured silicone composition in the heating step of the next step using a Baker film coater or the like. In this way, the long axis direction of the boron nitride can be oriented in the coating direction of the sheet-like semi-cured silicone composition (parallel to the coating surface). The thermally conductive silicone resin composition coated on the separator film is preferably uniformly coated to a thickness of 100 to 2000 μm, and more preferably uniformly coated to a thickness of 300 to 1000 μm.
[0045] Heating process (2) The heating step is a step of obtaining a sheet-like semi-cured silicone composition by heating the thermally conductive silicone resin composition applied to the separator in the coating step. If the thermally conductive silicone resin composition contains a solvent, the step of volatilizing the solvent component by heating is also included. The heating temperature of the heating step is preferably 40 to 100° C., more preferably 60 to 80° C. In addition, the heating time is preferably 1 to 30 minutes, more preferably 1 to 10 minutes.
[0046] Cutting process (2) The cutting step is a step of peeling the sheet-like semi-cured silicone composition obtained in the heating step from the release film and cutting it according to the size of the mold used in the next step of the molding step. It is preferred that the cutting size is 0.3 to 1.0 mm smaller in width and length than the internal size of the mold, so that the sheet-like semi-cured silicone composition can be easily filled in the next step of the molding step.
[0047] Forming process (2) (Molds used in the molding process) It is the same as the molding step (1).
[0048] (Filling method) The sheet-like semi-cured silicone composition obtained in the cutting step is filled in the lower mold in the following manner (i) or (ii). (i) The sheets of semi-cured silicone composition are aligned in the X-axis direction of the mold so that the coating flow direction becomes parallel to the X-axis direction of the mold, and are accumulated and filled in the Z-axis direction. (ii) The sheets of semi-cured silicone composition are aligned in the Y-axis direction of the mold so that the coating flow direction becomes parallel to the Y-axis direction of the mold, and are accumulated and filled in the Z-axis direction. In this manner, a molded body in which boron nitride is oriented can be obtained more preferably and efficiently. There is no particular restriction on the number of sheets of semi-cured silicone composition arranged in the X-axis direction or the Y-axis direction, and it can be appropriately determined according to the size of the lower mold, the size and thickness of the sheet of semi-cured silicone composition, etc. From the perspective of production capacity, for example, 1 to 10 sheets are preferred, and 1 to 5 sheets are more preferred. The number of the sheet-like semi-cured silicone composition deposited in the Z-axis direction is preferably 2 sheets (2 layers) or more, and more preferably 5 to 3000 sheets (5 to 3000 layers).
[0049] (Molding method) The molding step is a step of pressing the lower mold with the upper mold in the Z-axis direction and completely curing the sheet-like semi-cured silicone composition by heating to obtain a thermally conductive silicone molded body. As a pressurization method, it is preferable to gradually increase the pressure from atmospheric pressure to reach a desired pressure. The pressure for pressing the mold can be appropriately selected depending on the desired shape and hardness of the thermally conductive silicone molded body, and is preferably 0.1 to 20.0 MPa, and more preferably 0.5 to 5.0 MPa. The surface temperature of the lower mold when the mold is pressurized is preferably -10 to 40°C, more preferably 0 to 30°C. The lower mold surface temperature during curing of the sheet-like semi-cured silicone composition is preferably 50 to 200° C., more preferably 100 to 150° C. The curing time is preferably 1 minute to 24 hours, more preferably 5 minutes to 1 hour.
[0050] Slicing process (2) The slicing step is a step of slicing the thermally conductive silicone molded body obtained in the molding step to obtain an insulating thermally conductive sheet of a desired thickness. Specifically, in the molding step, when filling by the method (i), the molded body is sliced to a desired thickness in parallel with the YZ plane; when filling by the method (ii), the molded body is sliced to a desired thickness in parallel with the XZ plane, thereby obtaining an insulating thermally conductive sheet in which the length direction of boron nitride is oriented in the thickness direction of the sheet.
[0051] [Insulating heat conductive sheet] The insulating heat-conductive sheet of the present invention is preferably an insulating heat-conductive sheet having the following properties.
[0052] [Orientation degree] The orientation degree is the ratio of the peak intensity in the thickness direction of the insulating heat conductive sheet detected by X-ray diffraction, that is, the sum of the counts of [2θ=41-43°] / the sum of the counts of [2θ=25-27°], which is 1 or more, preferably 2 or more.
[0053] [hardness] From the viewpoint of operability and heat dissipation, the hardness of the insulating heat conductive sheet of the present invention is preferably an Asker C hardness of 20 to 60, and more preferably 20 to 40. If the Asker C hardness is less than 20, the sheet is easily deformed when handling the sheet, and the orientation may be damaged; if the Asker C hardness is greater than 60, the contact thermal resistance between the sheet and the heating element and the cooling element becomes larger.
[0054] [Thermal conductivity] The thermal conductivity of the insulating heat conductive sheet in the thickness direction is preferably 16 to 30 W / mK, more preferably 18 to 26 W / mK. The thermal conductivity is a value measured by a laser flash method (LFA447 Nanoflash manufactured by NETZSCH) in accordance with JIS R1611:2010.
[0055] [Dielectric breakdown voltage] The dielectric breakdown voltage of the insulating heat conductive sheet is preferably 5 kV / mm or more, and more preferably 8 kV / mm or more. The dielectric breakdown voltage is a value measured by a method in accordance with JIS C2110.
[0056] [proportion] The specific gravity of the insulating heat conductive sheet is preferably 1.2 to 2.0, more preferably 1.4 to 1.8. The specific gravity is a value measured at 25°C by a water displacement method using an automatic specific gravity measuring device (SGM-6, manufactured by Mettler) in accordance with JIS K6249:2003. [Example]
[0057] Hereinafter, the present invention will be specifically described using Examples and Comparative Examples, but the present invention is not limited to these Examples and Comparative Examples. The kinematic viscosity is a value measured at 25° C. using a Cannon Fenske viscometer according to JIS Z8803:2011, the aspect ratio is obtained by SEM measurement, and the average particle size is a cumulative average particle size (median particle size) based on volume measured by a particle size analyzer, Microtrac MT3300EXII, manufactured by Microtrac BEL.
[0058] (Preparation of Thermally Conductive Silicone Resin Composition) The components (A) to (C) used in the following examples are shown below.
[0059] Component (A1): an alkenyl group-containing organopolysiloxane represented by the following formula [Chemical formula 5] (A1-a) In the above formula, q is the kinematic viscosity at 25°C of 600 mm 2 The organopolysiloxane (A1-b) of which q in the above formula is a number such that the kinematic viscosity at 25° C. is 100,000 mm 2 / s number of organopolysiloxane
[0060] Component (A2): organohydrogenpolysiloxane (A2-a) represented by the following formula: [Chemical formula 6] (The order of the siloxane units in brackets is not fixed.) (A2-b) [Chemical formula 7]
[0061] (A3) Ingredients: 5% chloroplatinic acid 2-ethylhexanol solution
[0062] (B) Component: Average particle size and aspect ratio of boron nitride (B1) HSPD50 (average particle size 50 μm, aspect ratio 75, manufactured by Dandong Chemical Engineering Institute Co.) (B2) HSPD (average particle size 45 μm, aspect ratio 50, manufactured by Dandong Chemical Engineering Institute Co.) (B3) HSP (average particle size 40 μm, aspect ratio 30, manufactured by Dandong Chemical Engineering Institute Co.) (B4) GP (average particle size 8 μm, aspect ratio 10, manufactured by Nippon Denki Kagaku Kogyo, used for comparative example) (B5) PTX-60 (spherical aggregate powder with an average particle size of 55 μm and an aspect ratio of 1, manufactured by Mommentive Co., used in comparative examples)
[0063] Component (C): Toluene, used as a diluent during kneading
[0064] The given amounts of the components shown in Table 1 below were kneaded for 60 minutes using a planetary mixer to obtain a thermally conductive silicone composition.
[0065] Hereinafter, the molds used in Examples and Comparative Examples will be described with reference to the drawings. Figure 1 A perspective view showing a mold used in the filling step. Figure 2 Indicated in Figure 1 The mold used in the filling process is a cross-sectional view at line AA shown in FIG. The mold used in the filling process is a mold having a plurality of grooves parallel to the long axis direction of the mold with a width of 1.5 mm, a length of 50.0 mm, a depth of 2.5 mm, and a bottom surface shape of a semicircular groove. Figure 3 The exploded perspective view of the mold used in the molding process is shown. The mold used in the molding process is a mold having a lower mold and an upper mold. The inner dimensions of the lower mold are 33.0 mm in width (X axis), 52.0 mm in length (Y axis), and 50.0 mm in depth (Z axis), and the upper mold has a width of 32.9 mm (X axis), a length of 51.9 mm (Y axis), and a height of 40.0 mm (Z axis).
[0066] (Filling process) The thermally conductive silicone resin composition prepared above was filled so as to overflow from the groove of the mold used in the filling step, and then the overflowed portion was scraped off with a scraper.
[0067] (Vibration process) The molds filled with the thermally conductive silicone resin compositions of Examples 1 to 6 and Comparative Examples 1 to 8 were vibrated for 30 minutes using a table-top ultrasonic cleaner UT-106 manufactured by Sharp Corporation of Japan, at a water temperature of 25° C., a frequency of 37 kHz, and an output of 100%. The mold filled with the thermally conductive silicone resin composition of Comparative Example 9 was subjected to the subsequent heating step without the vibration step.
[0068] (Heating process) After the vibration step, the thermally conductive silicone resin composition in the mold was heated at 80° C. for 2 minutes to obtain a semi-cured silicone composition in the form of an elongated strip. In Comparative Example 9, the vibration step was omitted, and the thermally conductive silicone resin composition in the mold after the filling step was heated at 80° C. for 2 minutes to obtain a semi-cured silicone composition in the form of an elongated strip.
[0069] (Molding process) The elongated strips of semi-cured silicone composition were filled in a mold in such a manner that the length direction of the elongated strips was parallel to the Y-axis direction of the mold, and 21 rows were arranged in the X-axis direction, and 40 layers were formed in the Z-axis direction. Figure 3 The mold was placed in the lower mold of the mold. The mold was heated at 120° C. for 30 minutes while being pressurized at 1.0 MPa in the Z-axis direction using an oil press to obtain a molded body.
[0070] (Slicing process) The molded body was sliced with a utility knife in parallel with respect to the XZ plane to obtain a sheet.
[0071] Table 1 shows the results of the following evaluations of the sheets obtained in Examples 1 to 6 and Comparative Examples 1 to 9.
[0072] (hardness) The hardness of the sample sliced into 12 mm thick was measured at 25°C using an Asker C hardness tester.
[0073] (Thermal conductivity) The sheet cut into a thickness of 2 mm was punched out into a circular shape having a diameter of 12.7 mm. This was used as a test sheet, and the thermal conductivity of the test sheet was measured using a laser flash method (LFA447 Nanoflash manufactured by NETZSCH) in accordance with JIS R1611:2010.
[0074] (Dielectric Breakdown Voltage) The sheet cut into 1 mm thickness was immersed in oil, and the dielectric breakdown voltage was measured according to the method of JIS C2110 standard.
[0075] (proportion) The specific gravity of the sheet cut into 2 mm thickness at 25° C. was measured by the water displacement method using an automatic specific gravity measuring device (SGM-6, manufactured by Metler) in accordance with JIS K6249:2003.
[0076] (Orientation Degree) A sheet sliced into 2 mm thickness was punched out into a circle with a diameter of 12.7 mm and used as a test sheet. The tabletop powder X-ray diffraction device D2 PHASER2nd Generation manufactured by BRUKER JAPAN was used for measurement under the conditions of scanning range: 20-90°, step: 0.024°, sample rotation: 10 rpm, voltage: 30 kV, current: 10 mA, and the sum of the count values of 2θ=41~43° (100 face) and the sum of the count values of 25~27° (002 face) were calculated. The degree of orientation is defined by the following calculation formula. Orientation degree = sum of counts of [2θ = 41 to 43°] / sum of counts of [2θ = 25 to 27°]
[0077]
Table 1
[0078] As can be seen from Examples 1 to 3 and Comparative Examples 1 and 2, a sheet having an appropriate hardness can be obtained by adjusting the molar ratio of the hydrosilyl group of the component (A2) to the alkenyl group of the component (A1). On the other hand, as in Comparative Examples 5 and 6, when the ratio of the component (A2) is not appropriate, the hardness of the sheet becomes high and molding itself becomes difficult. On the other hand, as can be seen from Comparative Examples 7 and 8, if the content of boron nitride is too high, the hardness of the sheet becomes high, and if the content of boron nitride is too low, the thermal conductivity becomes low. It can be seen from Example 4, Example 5 and Comparative Example 3 that when the average particle size of boron nitride is 40 μm or more, a preferable thermal conductivity is achieved. In addition, the sheet of Comparative Example 9, which was manufactured without a vibration step and had an orientation degree of boron nitride in the thickness direction of the sheet of less than 1, failed to form a good heat conduction path and had a low thermal conductivity compared to the sheet of Example 2 in which the boron nitride content in the sheet was the same.
[0079] Description of Reference Numerals 10-Mold for filling process 11- Groove of the mold for the filling process 20-Molds used for molding process 1- Upper mold of the mold used for the molding process 2- The lower mold of the mold used for the molding process
Claims
1. An insulating thermally conductive sheet, which is a cured product of a thermally conductive silicone resin composition, comprising the following components (A) and (B), (A) 100 parts by mass of a thermosetting silicone resin containing the following (A1) to (A3), wherein: (A1) an organopolysiloxane having two or more alkenyl groups bonded to a silicon atom in one molecule, (A2) an organohydrogenpolysiloxane composed of the following (A2-a) and (A2-b), wherein the molar ratio of the total amount of hydrosilyl groups in the component (A2) to the alkenyl groups bonded to silicon atoms in the component (A1) is 0.7 to 1.2, (A2-a) an organohydrogenpolysiloxane represented by the following formula (a), [Chemical formula 1] In the formula, m is 2 or 3, n is a number from 10 to 50, and the bonding sequence of each siloxane unit bracketed by m and n may be block or random. (A2-b) an organohydrogenpolysiloxane represented by the following formula (b), [Chemical formula 2] In the formula, p is a number between 10 and 30. The molar ratio of the above-mentioned component (A2-a) to the component (A2-b) is (A2-a) component: (A2-b) component = 1:0.2 to 1:2, (A3) Hydrosilylation catalyst: an amount of 100 to 3000 ppm in terms of platinum group metal atoms relative to 100 parts by mass of the component (A1); (B) boron nitride having an average particle size of 40 to 100 μm and an aspect ratio of 20 to 100 as detected by a laser diffraction / scattering method: 150 to 500 parts by mass, The insulating heat conductive sheet has a degree of orientation in a thickness direction detected by an X-ray diffraction method that satisfies the sum of count values of [2θ=41 to 43°] / the sum of count values of [2θ=25 to 27°]=1 or more.
2. The insulating heat-conductive sheet according to claim 1, Its Asker C hardness is 20-60.
3. The insulating heat-conductive sheet according to claim 1 or 2, The thermal conductivity in the thickness direction is 16 to 30 W / mK.
4. The insulating heat-conductive sheet according to claim 1, Its insulation breakdown voltage is above 5kV / mm.
5. The insulating heat-conductive sheet according to claim 1, Its specific gravity is 1.2~2.0.
